ASD Pathogenesis and Emerging Treatments: Lessons Learned from the Monogenic Syndromic ASD - Dong, PhD, Cun-Jian; Kong, MD, Xuejun (North American Journal of Medicine and Science, 2017)
Autism Spectrum Disorder (ASD) is a group of complex neurodevelopmental disorders characterized by social impairments and repetitive behaviors. It can be divided into two major subcategories: 1) non-syndromic (sporadic or idiopathic) ASD and 2) syndromic ASD that also manifests other characteristic medical conditions and physical features. ASD is a growing public health crisis as its prevalence increases rapidly in recent years. There is no FDA approved drug for the treatment of ASD core symptoms that define the disorder, which is a major challenge in the management of ASD. This is largely due to the lack of a good understanding of its etiology that is highly complex and heterogeneous. Many types of the syndromic ASD are caused by mutations of a single gene (monogenic), which provides an excellent tool to explore the disease mechanisms leading to the pathogenesis of the core symptoms. Here, we briefly review the recent progress in animal studies on the disease mechanisms of the fragile X syndrome and the syndromes caused by loss of function of a key negative regulator along the mTOR signaling cascade due to the deleterious mutations of the respective gene. We emphasize the disrupted signaling pathways likely shared by some non-syndromic ASD cases, and highlight druggable targets and their translation for the treatment of ASD patients. [N A J Med Sci. 2017;10(4):148-155. DOI: 10.7156/najms.2017.1004148]